Cognitive Strategies and Social Attitudes That Perpetuate Gender Inequality in Secondary Education Students - Laura Pérez-Díaz; Macarena Blázquez-Alonso; Juan Manuel Moreno-Manso; María Guadalupe Lucas-Milán; Pilar Cantillo-Cordero; María Elena García-Baamonde (Social Sciences)
The research analyzed the cognitive styles, sexist attitudes and social competencies that hinder gender equality in secondary education students. It identified sexist attitudes, cognitive styles and social skills that hinder change towards gender equality; explored significant differences in sexist attitudes and cognitive strategies and social attitudes by age; studied the relationship between sexist attitudes and cognitive and social strategies that perpetuate gender inequality; and analyzed how age may predict the use of these strategies. A total of 1034 students aged 11 to 18 participated in a cross-sectional study. The Ambivalent Sexism Inventory for Adolescents and the Questionnaire of Attitudes and Cognitive Social Strategies were administered. The results indicate that young people exhibit moderate levels of cognitive and social strategies that hinder the change in sexist behaviors. At ages 12–14, the acceptance of ambivalent and benevolent attitudes such as paternalism and heterosexual intimacy increases. We found greater aggressiveness–stubbornness, apathy–withdrawal, impulsivity, and rigidity of thought at ages 15–17. Age explains a small proportion of the variance in sexist attitudes, cognitive styles, and social competencies that hinder gender equality. The study highlights the need for coeducational measures that ensure equal cognitive and socio-emotional development in women and men.